Method of action in the case of a public disturbance in public spaces - Caciula, Jeni Georgiana (Eximia, 2023)
Since the beginning of the first forms of human coexistence, the need for order and safety has undoubtedly become imperative. During the development of the state, the idea of public order was outlined in different ways, but it was always accompanied by the police law of the state. Until now, the consolidation of the state has relied on the maintenance of order and public safety. This concept is reflected in the state's focus on protecting social rights, life and integrity of citizens, compliance with established rules and other accepted values. Thanks to the authorities to which the state resorted, the priority of ensuring public order became satisfied, through the activities of preventing and countering antisocial phenomena. The complete realization of social equilibrium is disturbed by facts against which the forces must fix measures. Thus, the local police, one of the current institutions used by the state, constantly struggles with circumstances in which the action of law enforcement is required to restore peace. Whether acting alone or cooperating with other public safety maintenance forces, such as: the gendarmerie, the Romanian police, the courts, the local police respects a set of specific principles and rules that guide its activity in different fields. So, the duties of a policeman are reflected in the sectors of public order and peace, environmental protection, traffic on public roads, commercial activity, records of persons and other legally regulated areas. I believe that, for each area of activity, the police officer must follow a series of rules that protect him from errors in the intervention. The indispensability of knowing how to act in certain situations is determined by the fact that the legal provisions that illustrate the rights and obligations of the police officer do not subject to rules the difficulties regarding the procedures for intervention, behavior and reaction to incidents. The police force performs its service in the field, in particular, making direct contact with the population, and in this way it becomes the first frontier of confrontation with criminals. Therefore, the performance of a professional service is closely related to the manner in which a police officer acts in the interest of the community.